2014
DOI: 10.1038/srep05776
|View full text |Cite
|
Sign up to set email alerts
|

Late Eocene to early Oligocene quantitative paleotemperature record: Evidence from continental halite fluid inclusions

Abstract: Climate changes within Cenozoic extreme climate events such as the Paleocene–Eocene Thermal Maximum and the First Oligocene Glacial provide good opportunities to estimate the global climate trends in our present and future life. However, quantitative paleotemperatures data for Cenozoic climatic reconstruction are still lacking, hindering a better understanding of the past and future climate conditions. In this contribution, quantitative paleotemperatures were determined by fluid inclusion homogenization temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This approach was widely employed for direct, quantitative paleo-temperature reconstructions including examples from the Precambrian-Cambrian (Meng et al, 2011b), Silurian (Losey and Benison, 2000), Permian (Benison and Goldstein, 1999; Zambito and Benison, 2013), Paleogene (Meng et al, 2013;Zhao et al, 2014), Quaternary (Lowenstein et al, 1998(Lowenstein et al, , 1999 and modern settings (Roberts and Spencer, 1995).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach was widely employed for direct, quantitative paleo-temperature reconstructions including examples from the Precambrian-Cambrian (Meng et al, 2011b), Silurian (Losey and Benison, 2000), Permian (Benison and Goldstein, 1999; Zambito and Benison, 2013), Paleogene (Meng et al, 2013;Zhao et al, 2014), Quaternary (Lowenstein et al, 1998(Lowenstein et al, , 1999 and modern settings (Roberts and Spencer, 1995).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These evaporites have been dated by palynological means (Sattayarak et al, 1991;Smith et al, 1996;Racey and Goodall, 2009) and isotopic evidence (Hansen et al, 2002), as Albian to Cenomanian (roughly 112-93 Ma). Detailed petrological and sedimentological analyses demonstrated that the evaporitic rocks formed in a large isolated inland basin (Utha-Aroon, 1993;El Tabakh et al, 1999), that probably encountered marine flooding L.C. Wang et al, 2014;Wang et al, 2015).…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling nucleation method has been widely used for paleotemperature reconstruction in geological periods, including the Precambrian 49 , Silurian 50,51 , Permian 52,53 , Cretaceous 54,55 , Paleogene 56,57 , and Quaternary 3,46 . In this study, following detailed petrographic observations of halite samples from the salt field and a drill core in Lop Nur, the cooling nucleation method was used to obtain the homogenization temperature of fluid inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…They include global proxies, for instance the isotopic ratio between 18 O and 16 O in ice cores23 or in shell of fossil marine organisms45; and local proxies, such as tree rings studies678, palynological studies9, and fluid inclusions (FIs)101112. FIs are present in virtually all rocks on Earth.…”
mentioning
confidence: 99%